TUBERCULIN SKIN TEST AND INTERFERON-Î³ RELEASE ASSAY ON THE DIAGNOSIS OF TUBERCULOUS SPONDYLITIS - Hadid, Tsabita; Faris, Muhammad; Betty Agustina Tambunan; Caesaroy Afif Wibowo (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights TST and IGRA have a significant correlation with the diagnosis of patients with Tuberculous Spondylitis. Various factors may affect the results of TST and IGRA. Thus, the use of TST and IGRA can be adjusted according to the condition of the hospital, the availability of diagnostic tools, the health worker's physical examination results, and the patient's medical history. Abstract Background: Tuberculous spondylitis or Pott's disease is extrapulmonary tuberculosis that is still a concern to health workers because of the broad spectrum of its clinical symptoms. Delay in diagnosis is very common in this disease. Therefore, its diagnostic tool needs to be thoroughly reviewed to determine its effectiveness. The diagnostic tools studied in this study were Tuberculin Skin Test (TST) and Interferon-Î³ Release Assay (IGRA). Objective: To analyze the role of TST and IGRA as diagnostic tools for the diagnosis of tuberculous spondylitis. Material and Method: This study used a systematic review method to analyze topic-related kinds of literature written in English and Indonesian found on PubMed, Scopus, ProQuest, and Web of Science databases. The literature screening process was carried out based on the PRISMA 2020 Guidelines. Result: Sixteen types of literature were included for a total of 116 patients. TST was detected positive in 45 (63%) and negative in 21 (30%) of a total of 66 patients with Pott's disease. IGRA was detected positive in 51 (77%), negative in 8 (12%), and indeterminate in 2 (3%) of a total of 61 patients with Pott's disease. Conclusion: TST and IGRA results significantly correlate with the diagnosis of tuberculous spondylitis. Both tests are still relevant for use in the diagnosis of the disease. IGRA and TST are used according to the needs of health workers and patients' health backgrounds.